Implementasi Ekstrakurikuler untuk Meningkatkan Kreativitas Santri dalam Menulis Kaligrafi di Ponpes Riyadlus Sholihin Kota Probolinggo - Qodir, Abd; Muhammad, Devy Habibi (MASALIQ, 2025)
This study seeks to provide a comprehensive analysis of the implementation of calligraphy-focused extracurricular activities at Pondok Pesantren Riyadlus Sholihin, examining their role in enhancing students' creative capacities in Arabic calligraphy. Historically, calligraphy emerged as a means of venerating the Qur'anic verses, but its development over time has shifted towards emphasizing aesthetic values. The discipline of calligraphy encompasses several distinct styles, including khat naskhi, khat tsulus, khat diwani, khat diwani jali, khat riq’ah, khat farisi, and khat kufi. At Pondok Pesantren Riyadlus Sholihin, calligraphy is embedded within the framework of religious education, prioritizing the artful transcription of Qur'anic text. This research adopts a qualitative methodology with a descriptive orientation, employing analytical techniques to delve into the subject matter. The analytical framework utilized is derived from Miles and Huberman, encompassing stages such as data reduction, data presentation, conclusion formulation, and data verification. The findings underscore the substantial impact of calligraphy extracurricular programs at Pondok Pesantren Riyadlus Sholihin, located in Probolinggo City, in fostering students' creative expression and technical proficiency in calligraphy. Moreover, these activities extend beyond technical skill development, nurturing a deeper appreciation for Islamic art and cultural heritage through structured training and sustained mentorship.